Insurance companies and the financial crisis - Schich, Sebastian (OECD Publishing, 2010)
The current financial crisis may primarily be a banking crisis, and the solvency of the insurance sector as a whole does not appear to be threatened. Nonetheless, insurance companies have been affected, and in mostly adverse ways. For many insurers, direct exposure to the epicentre of the crisis, the US mortgage market, and to related securities appears to have been limited. But the financial crisis has nonetheless had an increasingly visible impact on the insurance industry, primarily through their investment portfolios, as the crisis spread and financial market valuations and the outlook for real activity deteriorated significantly. Also, a number of concentrated exposures to credit and market risks have been revealed, including in US mortgage and financial guarantee insurance companies, as well as in parts of certain other insurance-dominated financial groups. Thus, while insurers as a group may have cushioned rather than amplified the downward pressures during the financial crisis, some clearly have added to downward pressures. Financial instruments that were at the core of difficulties served an insurance function and, thus, it is not so surprising that some institutions from that sector have been affected by the crisis on one or the other side of their balance sheets
Keywords: Finance and Investment